Pengaruh Perlakuan Panas terhadap Kekerasan dan Kekasaran Permukaan Hasil Pembubutan Baja AISI 1045 - Fajar Y. Prabowo; Joko Waluyo; yudha, venditias (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2025)
This study examines the effects of heat treatment on the hardness, tensile strength, and surface roughness of AISI 1045 steel during turning operations. The material was tested under three conditions: untreated, hardened (with water and oil quenching), and tempered. Results reveal that heat treatment transformed the microstructure from ferrite-pearlite to a combination of martensite, bainite, ferrite, and pearlite. Hardness increased from 52.83 HRC (untreated) to 80.17 HRC (water-quenching hardening) and 68.33 HRC (oil-quenching hardening). Tempering achieved the highest tensile strength at 1231.73 MPa with a hardness of 65 HRC. Surface roughness was lowest for tempered specimens at 700 RPM (3.6 µm), while water-quenching hardening at 1000 RPM resulted in the highest roughness (35.35 µm). Tempering is recommended for machine components such as shafts due to its optimal balance of mechanical properties, hardness, and surface quality.